Sawkanakuy: Cognitive Aspects of Humor in Quechua - Ramos Tacca, Mario (2021)
This study is an approach to knowledge the humor cognitive processes in the Quechua language. It is a descriptive examination of communicative, experiential and corporeal acts of language with emphasis on the gestalt factors of euphoric behavior in Quechua speakers. Therefore, it aims to analyze cognitive schemas as processes that construct contextual meanings in a corpus from Apurímac, Cuzco and Puno carnival speeches.